Skin immunization with third-generation hepatitis B surface antigen using microneedles. Issue 40 (20th September 2019) - Nguyen, Thuy Trang; Choi, Jung-ah; Kim, Ji Seok; Park, Hayan; Yang, Eunji; Lee, Won Jun; Baek, Seung-Ki; Song, Manki; Park, Jung-Hwan
Abstract: L-HBsAg is a third-generation hepatitis vaccine capable of inducing antibodies in non-responders and thus providing potentially therapeutic treatment. In this study, L-HBsAg was administered using microneedles (MN) without an adjuvant to induce intradermal (ID) immunization, and the efficacy of ID immunization was compared with that of intramuscular (IM) immunization that uses a conventional formulation with an adjuvant of aluminum hydroxide (L-HBsAg-AL-IM). The L-HBsAg was dip-coated onto 800-μm-long microneedles made of polylactic acid (PLA). Delivery efficiency and administration time were determined through in vitro experiments using porcine skin. The denaturation of the formulation against sterilization by gamma rays was observed. A storage test and a freeze-thaw cycle test of the microneedles with trehalose as a stabilizer (L-HBsAg-MN-Tre) were observed. An antibody titer of L-HBsAg-MN-Tre was compared with that of the conventional IM immunization of the L-HBsAg solution with aluminum hydroxide (L-HBsAg-AL-IM). The formulation containing L-HBsAg was located on the upper third of the microneedle tips. The formulation on the MN was dissolved and delivered within 30 min of insertion into porcine skin in vitro . Trehalose was selected as a stabilizer, and the stabilizing effect increased with the increase of trehalose content in the solidified formulation. L-HBsAg-MN with 15% of trehalose was stable for 7 days at 40 °C and showed increased stability compared to the conventional liquid formulations. L-HBsAg-MN-Tre showed improved stability during the freeze-thaw cycle. The antibody titer of L-HBsAg-MN-Tre at 28 days was higher than that of L-HBsAg-AL-IM. ID administration of L-HBsAg-MN-Tre showed better efficacy and improved thermal and freeze thaw stability compared to L-HBsAg-AL-IM. Therefore, L-HBsAg-MN-Tre administration showed the possibility of ID delivery of L-HBsAg without the use of an adjuvant for the efficacy, convenience, and safety of pediatric vaccination.